Sakura : a novel - Nishi, Kanako, 1977- (HarperVia, 2026)
When Kaoru receives a letter from his estranged father announcing his return home to Osaka, he is drawn back to the house and memories he has long avoided. Once a close and seemingly perfect family, the Hasegawas were devastated by a tragic accident that fractured their bond and left them struggling with grief and distance. As Kaoru reconnects with his parents and siblings, the family must confront the pain of the past and find a way forward. Through it all, their loyal dog, Sakura, offers steady companionship and unexpected hope, helping them rediscover love, resilience, and the possibility of healing.